(untitled) (Research, Society and Development, 2021)
Introduction: Fetal hydrops is defined as the presence of abnormal fluid collections in two or more extravascular fetal compartments and body cavities. There are about 150 different underlying causes known today potentially leading to this fetal alteration. Objective: To analyze the etiologies involved in the occurrence of cases of fetal hydrops. Methods: A systematic literature review was carried out using the MedLine, Pubmed and Scielo databases, from 2015 to 2021, using the expressions: "fetal, hydrop, etiologies." Discussion: Fetal hydrops is divided into immune and non-immune. Immune results from anemia secondary to erythroblastosis by alloimmunization, so when there is maternal exposure to fetal antigens, it generates an immune response that results in the production of antibodies. History of blood transfusions, previous births, trauma and a history of alloimmunization are characterized as risk factors. Thus, immunoprophylaxis with anti-D immunoglobulin is indicated for all RhD negative pregnant women, with RhD positive male partner, with abundant fetal maternal hemorrhage during childbirth or events with potential sensitizer in the prenatal period. Conclusion: For an effective treatment, it is essential to identify the type of fetal hydrops in the patient and then the etiology of the disease, which is quite variable in Non-Immune Fetal Hydrops.